Antiphospholipid syndrome presenting as extensive skin ulcers on unilateral lower extremity: a case report - Yang, Yanan; Zhou, Yaoyao; Zhang, Lingyi; Pang, Mengru (Frontiers in Surgery, 2024)
Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by recurrent arterial and venous thrombosis, habitual fetal miscarriages, often accompanied by mild to moderate thrombocytopenia, and persistent moderate-to-high titer positivity for antiphospholipid antibodies (aPLs). However, patients with antiphospholipid antibodies may also present with several nonthrombotic clinical manifestations, such as thrombocytopenia, cardiac valve disease, nephropathy, skin ulcers, or cognitive dysfunction, which are collectively referred to as nonstandard manifestations of APS. Of these, for APS with predominantly cutaneous ulcers, previous reports have focused on APS with combined cutaneous vasculitis, and its medical treatment, rather than cutaneous ulcers with predominantly fatty inflammatory lesions, and the associated surgical treatment. Here, we admitted a relatively rare case of primary APS with extensive skin ulceration of the right lower extremity, without cutaneous vasculitis, in the presence of extensive and severe inflammatory lipoatrophy, carrying anti-β2-glycoprotein I and lupus anticoagulant, which is reported as follows, with a view to raising awareness of this disease.